Tinnitus emerging in the context of a COVID-19 infection seems not to differ in its characteristics from tinnitus unrelated to COVID-19 - Figueiredo, Ricardo R.; Penido, Norma de O.; Azevedo, Andréia A. de; Oliveira, Patrícia M. de; Siqueira, Adriana G. de; Figueiredo, Guilherme de M. R.; Schlee, Winfried; Langguth, Berthold (Frontiers in Neurology, 2022)
Background and aim COVID-19 is a respiratory disease caused by the new coronavirus SARS-CoV-2, for which the first cases were reported in China, by December 2019. The spectrum of clinical presentations is wide, ranging from asymptomatic cases to a severe acute respiratory syndrome, sometimes with multiple systems involvement. Viral infections, including those related to respiratory virus, may cause hearing loss and, by extent, considering its pathophysiology, tinnitus. A systematic review on inner ear related symptoms in patients with COVID-19 reported 4.5% occurrence rate of tinnitus, with high variance of prevalence between the studies. Our aim is to further explore the relationship between COVID-19 and tinnitus. For this purpose we analyzed a sample of people who had suffered from a COVID-19 infection in the city of Volta Redonda, Brazil. In detail, we compared those with new onset tinnitus during or after the COVID-19 infection with those without tinnitus and those with tinnitus onset before the COVID-19 infection. Methods Fifty-seven patients over 18 years old and previously diagnosed with COVID-19 confirmed by a RT-PCR test were included. Patients were subdivided in three groups: no tinnitus (NT), tinnitus that already existed before COVID-19 (chronic tinnitus, CT) and tinnitus that arose during or after COVID-19 (post-COVID-19 tinnitus, PCT). Data concerning COVID-19 symptoms, drugs prescribed for COVID-19, tinnitus characteristics, comorbidities and other otological symptoms were collected. For all the patients, tonal audiometry and otoacoustic emissions were performed. Tinnitus patients fulfilled the Tinnitus Handicap Inventory (THI) and visual-analog scales (VAS) for loudness and distress. Patients with CT answered a simple question about the worsening of their tinnitus after COVID-19. Results PCT was reported by 19.3% of the patients, while 22.8% reported CT. No statistical difference was found between CT and PCT concerning hearing function, tinnitus characteristics and tinnitus distress. There was also no statistically significant difference between PCT and NT with respect to COVID-19 symptoms and pharmacological COVID-19 treatment. Patients with CT reported worsening of their tinnitus after COVID-19. Conclusion As with other viral infections, inner ear symptoms may be associated with COVID-19. In our sample patients with tinnitus onset before COVID-19 and those with tinnitus onset during or after COVID-19 did not differ significantly in their clinical characteristics and their hearing function, suggesting that tinnitus occurring in the context of a COVID-19 infection is not related to a unique pathophysiological mechanism. The comparison of COVID-19 patients, who developed tinnitus with those who did not develop tinnitus did not reveal any differences in COVID-19 symptoms or COVID-19 treatment. Thus, there was no hint, that a specific expression of COVID-19 is closely related to post COVID-19 tinnitus onset. Although some drugs used to treat tinnitus are known to damage the inner ear cells (especially hydroxychloroquine), we did not see any relationship between the intake of these drugs and tinnitus onset, eventually due to the short prescription time and low doses. Among those patients who had tinnitus before COVID-19 30,8% reported worsening after COVID-19. Overall, tinnitus emerging in the context of a COVID-19 infection seems not to differ from tinnitus unrelated to COVID-19. For further exploring the relationship of tinnitus and COVID-19, large population based studies are warranted.